2020
DOI: 10.3389/fmicb.2020.01824
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of cmcp Gene as a Pathogenicity Factor of Ceratocystis manginecans

Abstract: Ceratocystis manginecans causes mango wilt with significant economic losses. In the infection court, cerato-platanin (CP) family proteins (CPPs) are believed to involve in pathogenesis but has not been determined in C. manginecans. To confirm this function, a CP protein (CmCP) of C. manginecans was characterized in this study. A protoplast of C. manginecans was prepared by treating its mycelia with driselase and lysing enzymes. The cmcp gene was edited using CRISPR/Cas-U6-1 expression vectors in 60% PEG and 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…that opens the door for possibilities of producing knockout mutants in C. destructans . These include agrobacterium-based transformation 42 , 43 and the CRISPR based method 44 .…”
Section: Resultsmentioning
confidence: 99%
“…that opens the door for possibilities of producing knockout mutants in C. destructans . These include agrobacterium-based transformation 42 , 43 and the CRISPR based method 44 .…”
Section: Resultsmentioning
confidence: 99%
“…GSEA showed that the DEGs were enriched in the microtubule-related complex, ATPase activity, hormone signal transduction pathway, and plant-pathogen interaction pathway. Microtubules and associated complexes play important roles in viruses subverting host cell mechanisms, replication, and transmission [30,31]. Many DEGs in the lemon's response to CYVCV are enriched in functions related to cytoskeletal protein binding and microtubule motor activity.…”
Section: Discussionmentioning
confidence: 99%